Comparison of the fermentation process of cocoa beans in different collection centers and its impact on the final quality (Agroindustrial Science, 2025)
The objective of this research was to compare the fermentation process in collection centers for bean quality in the Bolívar canton. The fermentation conditions at each center were assessed using observation sheets. A total of 120 random samples of dry beans were taken from different batches. The physical quality of the beans was initially evaluated based on their shape, color, and aroma. Cutting tests were conducted to inspect the interior of the grains and classify them based on their fermentation. The Kruskal-Wallis test revealed significant differences in the level of fermentation between the centres, with C2 showing the highest level and C4 the lowest. Likewise, C2 showed a greater number of samples classified as grade 1, suggesting higher quality fermentation. The Chi-square test indicated a significant association between the centres and the degree of fermentation, although the Cramer's V index showed that this relationship is not decisive. These results indicate that, in addition to fermentation practices, factors such as soil quality, climate, altitude and the maturity of the cocoa pods influence final grain quality.
Keywords: physical quality; cutting test; fermented grains; fermentation degree